2003
DOI: 10.1021/jf030292y
|View full text |Cite
|
Sign up to set email alerts
|

Insect Antifeedants from Munronia henryi:  Structure of Munroniamide

Abstract: A novel A,B-seco-tetranortriterpenoid lactam, named munroniamide (1), along with three known ceramides (2-4), was isolated from the methanolic extract of the whole bodies of Munronia henryi. The structure of 1 was established using spectroscopic methods. Compound 2 exhibited significant antifeeding activity, and 1 exhibited moderate activity, whereas 3 and 4 showed negative activity against Pieris brassicae L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…The proved that the reduction in growth of the larvae was not entirely due to antifeedent, but partly due to the toxic effects of the aglaroxin A compound. Qi et al (2003) have been identified compound munroniamide from Munronia henryi and that has proved antifeedent activity against Pieris brassicae L.…”
Section: Biological Activities Of Meliaceae Plants Against Lepidoptermentioning
confidence: 99%
“…The proved that the reduction in growth of the larvae was not entirely due to antifeedent, but partly due to the toxic effects of the aglaroxin A compound. Qi et al (2003) have been identified compound munroniamide from Munronia henryi and that has proved antifeedent activity against Pieris brassicae L.…”
Section: Biological Activities Of Meliaceae Plants Against Lepidoptermentioning
confidence: 99%
“…The antifeedant properties of limonoids from Melia azederach (chinaberry), and related plants, have been reviewed (Nakatani 1999). Other tetranortriterpenes such as nymania-3 from Dysoxylum malabaricum (Govindachari et al 1999), hirtin derivatives from Trichilia palida (Simmonds et al 2001), munroniamide from Munronya henryi (Qi et al 2003) and xyloccensins A-K and xylogranatins A-R from species of the Xylocarpus genus (Wu et al 2008;Shen et al 2009) act as feeding deterrents. Triterpenes of this type from the Meliaceae and Rutaceae groups have been tested showing that the orientation of the furan group and the hydroxylation of specific carbons affect their antifeedant properties against the fall armyworm (Spodoptera litura; Suresh et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…1 Up to now, some phytochemical studies have been reported on M. delavayi [2][3][4][5] and M. henryi [6][7][8][9] , and tetranortriterpenoids and triterpenoids are their main components. Especially, tetranortriterpenoids exhibit chemical defensive function in nature, such as antibacterium, antifungal, 2 and antifeeding 8 activities.…”
Section: Introductionmentioning
confidence: 99%